Social Media Website with Python using Django - Shreyanjali, P.B.; Usha Sree, R.; Hushalictmy, P. (INTI International University, 2024)
It is a popular and powerful platform for users. Millions of people have their ideas and thoughts which they can share on several aspects of their daily lives. Social media can generate huge amounts of public responses in the form of likes, comments, replies, saved images, etc. We developed a web application with user interfaces using Python with Django framework which showcases the social trends. Django collects all the user data and stores it in Django administration. This research has proposed a platform where the user can share their images, videos, and thoughts. This is the platform where the user can follow other users whom they know and even they can view the other's creativity which they have posted on social media. Our model analyzes and stores real-time data. Social media websites have been implemented by several programming languages such as HTML, CSS, JavaScript, Python, and Django framework was used to design the web pages.